Modeling an incentive management system for research and teaching staff at the University - Юлия Мунирова; Елена Ростова (Вестник Пермского университета: Серия Экономика)
Introduction. The article considers the current situation with the incentive part of remuneration for the university teachers. An important component of the scientific activity at the university is analyzed, which is an innovative activity associated with a more dynamic academic performance. The relevance of the research arises from the need to manage personnel training for the technological sovereignty of the country. This requires new efforts and entails costs for the teaching staff, which, in its turn, calls for the revised motivation systems for innovative activity. Purpose. The article is aimed at describing an incentive system for research and teaching staff and formalizing the functions of the participants with a performance-based employment contract. Materials and Methods. The materials of the study are the terms and conditions stated in the performance-based employment contracts at the Universities in Samara region and the incentive system for research and teaching staff. Methodologically, the research refers to game theory; coalition games are also considered. The article analyzes possible situations typical for the relationships between the University Administration and teachers motivated to intensify innovative and scientific activities. Results. The authors managed to formalize the task of calculating incentive effects in a multi-agent motivation management system for university employees when a performance-based employment contract between the University Administration (Center) and different age groups of teachers (Agents) is prepared. Some restrictions, tolerance regions, have been identified for each participant in labour-management relations arising in the course of the University’s economic activity; adequate performance functions are plotted. Conclusions. The authors present a project of a multi-agent single-level system for motivation management among teachers when a performance-based employment contract is prepared. The obtained analytical management models account for the results of different groups of teachers from their planned innovative activities in higher education institutions. The next stage of the study is supposed to determine the types of functions characterizing the profit (loss) from each participant in the system to specify their innovative activities and interact between the Center and Agents when the external environment and its requirements are changing.